Covariation between eggshell colouration and eggshell bacteria abundance and egg characteristics in blackbirds. Issue 3 (4th May 2019) - Hoi, Herbert; Darolová, Alžbeta; Krištofík, Ján; Poláček, Miroslav; Majtán, Juraj; Zeman, Michal; Okuliarová, Monika; Turčoková, Lucia; Knauer, Felix
Abstract : Several functions have been proposed to explain eggshell colouration in birds. Eggshell colour may, for instance, signal female egg investment and hence the quality of the female and/or the egg. Such a covariation between eggshell colour and egg quality is supported by several studies, but what is related to eggshell colour is not necessarily consistent between populations, species or egg compounds. In this study, we examined several maternally derived egg compounds; namely yolk mass, egg white lysozyme and pH, yolk testosterone, oestrogens and eggshell colour and we determined the abundance of cultivable bacteria on the eggshell surface of blackbirds' eggs Turdus merula . Based on that, we examined whether there is an association between eggshell colour parameters derived via spectrophotometric analyses and eggshell spot size and any of the investigated egg parameters. Our results suggest that two eggshell colour components derived by a principle component analyses and eggshell spot size covary with different egg parameters. We found that eggs containing more UV, yellow and red chroma in their eggshells contain heavier yolks. In contrast more bluish, greener and brighter eggs have to face higher loads of bacteria i.p. haemolytic bacteria and bacteria originating from the urogenital tract of the female. No other egg compound investigated seemed to be reflected in any eggshell colour parameter. Our data do not support an antibacterial function of eggshell colour as the abundance of bacteria originating from the female urogenital tract is negatively related to eggshell colouration. Furthermore, we found a positive but weak association between egg spot size and egg white lysozyme levels. Possible functional implications of our results are discussed.